Economic study and energy analysis of a thermal power plant for the generation of biodisesel. (2022) - Meza, Jhonatan; Jose, Deepa; Anthoniraj, S.
Abstract 1 : This article t is an investment model for a biodiesel plant of less than 1 Megawatts in size, where economic aspects such as investment, operating costs and the price of Kilowatts installed are considered, taking as a difference the price of different brands of generators In the Ecuadorian and European markets and considering the feasibility of the investment with an economic analysis.